Improving Singing Skills Using the Solfegio Method in Students in Padang City Elementary School - Jagar Lumbantoruan; Hengki Armez Hidayat (Fakultas Bahasa dan Seni UNP, 2023)
Indonesian National Education aims to develop all the potential of students so that they can be applied and used in real life. Singing as a material, tool, and resource in art education in elementary schools is carried out to balance aesthetic, creative, expressive, and appreciative knowledge. Although singing lessons have been implemented, the knowledge and skills required are not by the planned objectives. Students are not yet skilled in singing in harmony because the rhythm and melody underlying the song lyrics are not appropriate. The purpose of the study was to try out the solfeggio method, namely the practice of reading songs according to rhythm and melody. The research design, namely: 1. Identify students' initial abilities and needs. 2. Designing the required learning materials, 3. Carrying out learning using the solfeggio method in a structured and graded manner. The results of the study are (a) students understand notes, beats, bars, and tempos and are skilled at reading song rhythms, (b) students understand notes, scales, pitch intervals, and chords and are skilled at reading song melodies, (c) students are skilled at singing in harmony according to rhythm and melody.